Experimental Study Of In-Plane And Out-Of-Plane Behavior Of Pp-Band Retrofitted Masonry Wallette Made Of Shapeless Stones - Sakurai, K.; Sathiparan, N.; Meguro, K. (My University, 2010)
Unreinforced masonry structure is one of the most popularly used constructions in the world, especially in developing countries. It is also unfortunately, the most vulnerable to the earthquake. In this research, we conducted a series of experiments to verify the suitability of PP-band retrofitting for masonry structures made of shapeless stones. Material tests were conducted to understand the basic parameters of stone masonry, i.e. shear, tension and compression strength. After the material tests, diagonal compression test and out-of-plane test were carried out using masonry wallette made of shapeless stones with and without retrofitting. From both test results, it was clear that PP-band retrofitting improved drastically the overall stability and ductility of stone masonry structures made of shapeless stones
Keywords: Stone Masonry; PP-band Retrofitting